Perancangan Application Programming Interface (API) Berbasis Web Menggunakan Gaya Arsitektur Representational State Transfer (REST) Untuk Pengembangan Sistem Informasi Administrasi Pasien Klinik Perawatan Kulit - Hijriani, Astria; Junaidi, Akmal; Pranata, Beni Adi (Universitas Lampung, 2018)
Application Programming Interface (API) is an interface built by system developer so some or entire functions of the system can programatically be accessed. Representational State Transfer (REST) is one of API development architectural style that uses Hypertext Transfer Protocol (HTTP) for data communication. This research implemented REST in developing API as the back-end of the skincare clinic patient information system. API was developed using Javascript Object Notation (JSON) as the standard format for data communication and JSON Web Token (JWT) as user authentication code. This research indicates that the development of API successfully performed on the patient administration of skin care clinic and implementation of REST makes it easy to develop API structures. This research produced REST API-based back-end for the patient administration information system of skin care clinic. API was tested in three stages: JWT testing on multiple back-end servers, API testing with Equivalence Partitioning and system functional testing.Â Keywords: application programming interface (api), hypertext transfer protocol (http), javascript object notation (json), json web token (jwt), representational state transfer (rest).